Work-based learning and capability development of machining workers in an automotive company - Mohd Yunus, Azmir (2016)
The phenomenon of individuals entering the labor market without relevant qualifications is common in Malaysia. Many people choose to work instead of pursuing further education after secondary school. In the labor market, these individuals are considered to be low skilled because they had no training prior to employment. For those who begin employment without formal training, skill formation is likely to occur at the workplace through work-based learning. However, despite the apparent pervasiveness of work-based learning, its potential as an approach for developing individuals who lack formal education has not been fully explored.